THE CONCEPT OF POLITENESS IN RUSSIAN AND UZBEK - Omonbayev Oybek Kholbutayevich (Journal Park Publishing, 2022)
The article explores the problems of speech etiquette in the Uzbek language on the material of treatment and motivation using the personal pronoun in the singular and plural (sizni and siz-you, You;) the specifics of their use in speech situations of communication between parents and children, between spouses, etc. are identified and noted; differences in the use of the same etiquette expressions by native speakers of different dialects of the Uzbek language are demonstrated.
Keywords: politeness, concept, linguoculture